Allyship with Indigenous Peoples as a Practice of Resistance in Nursing: Uniting Our Voices - Blanchet Garneau, Amélie; Gill, Joannie; Cassivi, Christine; Collin, Shenda (Aporia, 2026)
Allyship is increasingly recognized as a key concept in nursing to support the rights, resurgence, and healing of Indigenous Peoples. It is presented as a practice of resistance that challenges settler colonialism, disrupts the status quo, and fosters social justice. Yet, allyship remains difficult to define and operationalize in practice. This discussion paper contributes to the critical reflection on allyship by exploring its meaning and practice in nursing. The paper draws on a dialogue among two Indigenous graduate nursing students, one white graduate student, and one white professor, who share their experiences and perspectives through a series of questions on the definition of allyship, identity, engagement, and challenges. Grounded in lived and professional experiences and the literature, the paper positions allyship as both an individual and systemic commitment. It calls on nurses to actively resist Indigenous-specific racism and take part in the collective effort toward Indigenous self-determination, healing, and justice.